A Comparative Study of China’s Public Diplomacy Toward Indonesia: During the Presidencies of Hu Jintao and XI Jinping - Pricillia, Herdiani Narita (Journal Research of Social Science, Economics, and Management, 2025)
Chinese public diplomacy toward Indonesia represents a charm offensive within its soft power strategy to enhance its status and cultural image. This effort is driven by the rising interest of Indonesians in the Chinese language and culture, despite China’s presence often being perceived as aggressive in international relations through public diplomacy. This research aims to analyze China’s public diplomacy toward Indonesia under the administrations of Hu Jintao and Xi Jinping, using the concept of public diplomacy. The methodology employs a qualitative comparative research design utilizing internet-based and document-based data collection techniques, analyzing official government documents, policy statements, media reports, and academic publications from both Chinese and Indonesian sources spanning the two presidential periods. Findings show both administrations employed five key indicators: time, purpose, media/public opinion, and instruments of public diplomacy such as branding, cultural diplomacy, and exchange. The comparison reveals three major differences: instruments, agents, and targets. Under Hu Jintao, the Chinese government was the dominant actor, with the main goal of disseminating culture. In contrast, during Xi Jinping’s era, non-state actors and mass media collaboration complemented government involvement, with the broader objective of enhancing and promoting China’s branding. The Confucius Institute served as the primary instrument in both eras, though the products and programs differed. Hu Jintao’s period emphasized cultural exhibitions, while Xi Jinping’s diplomacy relied more on social media and internet platforms to reach wider audiences. Overall, China’s evolving approach reflects a shift from cultural dissemination to strategic branding and influence-building in Indonesia.